Effects of diacylglycerol O-acyltransferase 1 (DGAT1) on endoplasmic reticulum stress and inflammatory responses in adipose tissue of ketotic dairy cows - Xu, Qiushi; Fan, Yunhui; Loor, Juan J.; Jiang, Qianming; Zheng, Xidan; Wang, Zhijie; Yang, Tong; Sun, Xudong; Jia, Hongdou; Li, Xinwei; Xu, Chuang (Journal of dairy science, 2022)
Adipose tissue of ketotic dairy cows exhibits greater lipolytic rate and signs of inflammation, which further aggravate the metabolic disorder. In nonruminants, the endoplasmic reticulum (ER) is a key organelle coordinating metabolic adaptations and cellular functions; thus, disturbances known as ER stress lead to inflammation and contribute to metabolic disorders. Enhanced activity of diacylglycerol O-acyltransferase 1 (DGAT1) in murine adipocytes undergoing lipolysis alleviated ER stress and inflammation. The aim of the present study was to investigate the potential role of DGAT1 on ER stress and inflammatory response of bovine adipose tissue in vivo and in vitro. Adipose tissue and blood samples were collected from cows diagnosed as clinically ketotic (n = 15) or healthy (n = 15) following a veterinary evaluation based on clinical symptoms and serum concentrations of β-hydroxybutyrate, which were 4.05 (interquartile range = 0.46) and 0.52 mM (interquartile range = 0.14), respectively. Protein abundance of DGAT1 was greater in adipose tissue of ketotic cows. Among ER stress proteins measured, ratios of phosphorylated PKR-like ER kinase (p-PERK) to PERK and phosphorylated inositol-requiring enzyme 1 (p-IRE1) to IRE1, and protein abundance of cleaved ATF6 protein were greater in adipose tissue of ketotic cows. Furthermore, ratios of phosphorylated RELA subunit of NF-κB (p-RELA) to RELA and phosphorylated c-jun N-terminal kinase (p-JNK) to JNK were greater, whereas protein abundance of NF-κB inhibitor α (NFKBIA) was lower in adipose tissue of ketotic cows. In addition, mRNA abundance of proinflammatory cytokines including TNF and IL-6 was greater in adipose tissue of ketotic cows. To better address mechanistic aspects of these responses, primary bovine adipocytes isolated from the harvested adipose tissue of healthy cows were subjected to lipolysis-stimulating conditions via incubation with 1 μM epinephrine (EPI) for 2 h. In another experiment, adipocytes were cultured with DGAT1 overexpression adenovirus and DGAT1 small interfering RNA for 48 h, respectively, followed by EPI (1 μM) exposure for 2 h. Treatment with EPI led to greater ratios of p-PERK to PERK, p-IRE1 to IRE1, p-RELA to RELA, p-JNK to JNK, and cleaved ATF6 protein, whereas EPI stimulation inhibited protein abundance of NFKBIA. Furthermore, treatment with EPI upregulated the secretion of proinflammatory cytokines into culture medium, including TNF-α and IL-6. Overexpression of DGAT1 in EPI-treated adipocytes attenuated ER stress, the activation of NF-κB and JNK signaling pathways, and the secretion of inflammatory cytokines. In contrast, silencing DGAT1 further aggravated EPI-induced ER stress and inflammatory responses. Overall, these data indicated that activation of DGAT1 may act as an adaptive mechanism to dampen metabolic dysregulation in adipose tissue. As such, it contributes to relief from ER stress and inflammatory responses.